(untitled) (Dhaka University Journal of Science, 2020)
Unmet need for family planning (FP) is responsible for lowering contraceptive rate which elevate unwanted pregnancy that have adverse effects on maternal and child health. This study uses Bangladesh Demographic Health Survey, 2014 data in order to identify the factors that are associated with unmet need for FP in Bangladesh. Since the survey is observational, a case-control data has been used matched by age and education of the respondents and the analysis was carried out by using a conditional logistic regression. Unmet need for FP was found to be higher in the rural area, among Muslims, among women who were not exposed to media or not member of any NGO, among couples having no sons. Dhaka Univ. J. Sci. 68(2): 149-153, 2020 (July)